Hubungan Dukungan Keluarga Dengan Tingkat Kecemasan Pada Persalinan Normal Masa Pandemi COVID-19 Di RSKD Ibu Dan Anak Pertiwi Kota Makassar - Herlianty Herlianty; Evi Sri Dahrianti; Ni Ketut Sumidawati (Jurnal Kesehatan Medika Udayana, 2022)
Mothers who undergo normal delivery during the COVID-19 pandemic can experience severe anxiety because the Corona Virus Disease-19 virus can also cause severe respiratory infections, such as lung infections (pneumonia). This virus can attack anyone, including pregnant women and babies is a potential or actual threat to a person's integrity that can evoke physiological and psychological stress reactions. The purpose of this study was to determine connetion between family support and anxiety levels during normal delivery on the COVID-19 pandemic at the Mother and Child Hospital Mother and Child Makassar.. Methods: The research design used wasresearch descriptive correlational through aapproach the cross-sectional. number of respondents in this study was 35 respondents with a sample of 35 respondents and the sampling technique used in this study was total sampling by taking all samples in the population. This research was conducted on 16 oktober - 2 November 2021. The instrument used was a questionnaire sheet distributed to respondents Results: The results of this study were processed using SPPSS 22. The results of the analysis with somers'd test obtained p value = 0.000 < value a=0.05. From this analysis, it can be interpreted that Ha is accepted and Ho is rejected, meaning that there is a connetion between family support and anxiety levels in normal delivery during the COVID-19 pandemic. Conclusion: For this reason, it is important to provide counseling and motivation to patients with normal delivery during the COVID-19 pandemic in increasing family support and decreasing anxiety in dealing with childbirth